Topology influence on the radio communication range of sensor networks - Tsvetanov, F.; Georgieva, I.; Pandurski, M. (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The Internet of Things (IoT) applications use wireless technologies in order to establish Internet connection. Communication technologies such as Wi-Fi, cellular, ZigBee, Bluetooth, etc. are used to transfer data in IoT. The choice of the appropriate technology or combination of technologies depends on the type of application, its characteristics, user requirements, and other factors such as communication range, security requirements, battery life, etc. In our project, we will focus on Star, Cluster and Mesh wireless topologies, conduct comparative analysis between them, and testing different XBee devices with specialized software. The experiments are connected to the quality of the transferred data using different XBee devices and how this will affect the transmission range. The results of our research show that in terms of the range and quality of packet transmission, the cluster topology shows the best results.